Breakfast in Latin America: Evaluation of Nutrient and Food Group Intake Toward a Nutrient-Based Recommendation - Kovalskys, Irina (2021)
Background: Little is known about breakfast habits of the Latin American (LA) population to support nutritional recommendations for a balanced breakfast in this region. Objective: To evaluate the nutritional composition of breakfast in the LA population and to propose recommendations for a balanced breakfast. Design: This multicenter cross-sectional study evaluated food and nutrient intake of nationally representative samples of urban populations of 8 LA countries (Argentina, Brazil, Chile, Colombia, Costa Rica, Ecuador, Peru, and Venezuela) in 2014-2015. Participants/setting: The sample comprised 8714 participants from the Latin American Study of Nutrition and Health, aged 15 to 65 years, randomly recruited according to geographical location, sex, age, and socioeconomic level. Main outcome measures: Two 24-hour recalls were used to examine dietary intake. Breakfast consumers were stratified by tertiles of Nutrient-Rich Foods Index 9.3 (NRF9.3) to assess the overall diet quality of individuals. Nutrient intake at breakfast of those in the upper tertile of NRF9.3 pooled for the 8 countries was used as a reference for the development of recommendations for LA adolescents and adults. Statistical analyses: Comparison of food and nutrient intake of breakfast across NRF9.3 tertiles were analyzed using the Kruskal-Wallis rank sum test. Results: Overall breakfast was an important contributor to protein, carbohydrate, and B vitamin intakes but also to added sugar and total and saturated fat intakes relative to daily intakes. Individuals in the upper NRF9.3 tertile had higher intake of key micronutrients such as calcium and potassium at breakfast compared with other tertiles. White breads/rolls/tortillas were the most consumed food group (60%), followed by butter/margarine (40%) and coffee/tea without milk (34%-50%). Conclusions: Breakfast contributed to the daily intake of B vitamins, protein, and carbohydrates but also added sugar and total and saturated fat intakes for all countries. The proposed recommendations support the nutrient density of existing highest-quality breakfast in the LA population while addressing concerns about nutrients to be encouraged or reduced.